2015
DOI: 10.1152/ajpgi.00234.2014
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 attenuates gastrointestinal inflammation and experimental colitis pathogenesis

Abstract: IC. Caspase-11 attenuates gastrointestinal inflammation and experimental colitis pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 56 publications
5
77
1
Order By: Relevance
“…Recent studies have also demonstrated a requirement for caspase 11 in mediating resistance against dextran sulfate sodium (DSS)-induced intestinal inflammation in mice 69-71 . Whether IL-1β and IL-18 are contributing factors in this case is contentious, with both similar and reduced levels of IL-1β and IL-18 being reported in caspase 11-deficient mice treated with DSS compared with treated wild-type mice 70, 71 . Differences in gut microbiota harboured by mice housed in different facilities and differences in experimental conditions could account for these discrepancies.…”
Section: Pyroptosis and Other Effector Functionsmentioning
confidence: 75%
“…Recent studies have also demonstrated a requirement for caspase 11 in mediating resistance against dextran sulfate sodium (DSS)-induced intestinal inflammation in mice 69-71 . Whether IL-1β and IL-18 are contributing factors in this case is contentious, with both similar and reduced levels of IL-1β and IL-18 being reported in caspase 11-deficient mice treated with DSS compared with treated wild-type mice 70, 71 . Differences in gut microbiota harboured by mice housed in different facilities and differences in experimental conditions could account for these discrepancies.…”
Section: Pyroptosis and Other Effector Functionsmentioning
confidence: 75%
“…Here we utilized Irak-m −/− mice in an acute colitis model induced with 5% DSS (Okayasu et al, 1990). This is a standard model utilized previously by our laboratory in similar studies evaluating mediators of innate immunity in IBD (Williams et al, 2015a, Williams et al, 2015b, Allen et al, 2012, Allen et al, 2010). We found that Irak-m −/− mice are protected in this experimental colitis model (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess acute experimental colitis, mice were given either 3 or 5% DSS dissolved in drinking water available ad libitum for 5 days as previously described (Williams et al, 2015b, Schneider, 2013). On day 5, mice were withdrawn from DSS and given regular drinking water ad libitum until euthanasia was performed on day 7.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations